Assessing the Transition from Survival to Sustainability: Case of Wechiau Community Hippo Sanctuary in Upper West Region of Ghana, West Africa (2013)
In the past 50 years, humans have changed ecosystems more rapidly to meet growing demands for food, fresh water, timber, fibre and fuel. This has resulted in substantial decrease in biodiversity, including the hippopotamus (hippo) population. There are currently about 150,000 hippos left in the world. Their status will change from vulnerable to endangered if threats are not controlled. The threats include destructive exploration and exploitation for human survival through hunting for ivory and meat, habitat loss due to flooding and destruction of hippo lawns along river banks. Sustainable exploration of biodiversity on the other hand ensures a balance in nature through synergistic cooperation in ecosystem services, human well-being as well as the direct and indirect drivers of change. This study assessed the emerging transition from survival to sustainability in the management of community-based biodiversity management in Ghana. Ghana has two hippo populations; one at Bui National Park and the other at the Wechiau Community Hippo Sanctuary (WCHS). The WCHS was established in 1998. It was chosen for in-depth analysis and assessment. The ecosystem assessment framework of interaction between ecosystems and drivers of global change was adopted for the study. The assessment was based on “before” and “now” scenarios to draw inferences for impact of community-based biodiversity management and sustainability. The WCHS provides economic alternatives to converting community-based ecosystems into sustainable economic ventures, including eco-tourism. The number of tourists to WCHS that stood at less than 500 persons in 2002 increased to 2,390 persons in 2011. The test of correlation between the number of local and foreign tourists revealed significant (p<0.001; ρ = 0.926) relationships in the influx of tourists to WCHS. This is evident by the increase in revenue that accrued to the WCHS. It also generated peaceful cohesion and aesthetics of the environment and development of property rights. The WCHS has led to the reduction in poverty and hunger through the generation of incomes, improvement in health through infrastructural provision, and biodiversity sustainability of local species. The case of WCHS demonstrates that biodiversity management founded on good communal relationships cannot only improve the livelihoods of the rural poor but also increase their resilience to face challenges as the people become more economically and socially resilient, and empowered to handle future threats to ecological imbalances.